Implementation of Just Energy Transition Partnership (JETP) Indonesia - Andini Maulifa Rizqia; Ica Wulansari (Jurnal Manajemen dan Bisnis Madani, 2026)
The Just Energy Transition Partnership (JETP) was introduced in Indonesia during the G20 Summit in Bali in 2022 as a global framework to accelerate the clean energy transition. Indonesia’s high dependence on fossil fuels has intensified the urgency for renewable energy, making energy sovereignty a national priority. With USD 20 billion pledged, JETP aims to retire coal-fired power plants early and expand renewable energy. However, this study argues that JETP risks undermining Indonesia’s energy independence by creating new debt and technological dependency. Using a qualitative descriptive approach and secondary data from international agencies, government reports, and academic research, the study analyzes JETP implementation in Indonesia. Findings show that most financing is loan-based, which increases Indonesia’s fiscal burden while contributing little to renewable deployment. This raises concerns over energy dependency, limited poverty alleviation, and unequal energy access. Without structural reforms in financing and technology transfer, JETP could reinforce dependency rather than support a just and sustainable transition. Therefore, the research highlights the importance of transparent governance, equitable financial mechanisms, and stronger domestic capacity building to ensure that the partnership genuinely aligns with Indonesia’s long-term goals of energy sovereignty, economic resilience, and inclusive development while promoting fairness, innovation, and self-reliance in Indonesia’s clean energy transformation.